From madness to mental health : psychiatric disorder and its treatment in Western civilization - Eghigian, Greg, 1961- (Rutgers University Press, 2010)
A unique anthology of readings, from ancient times to the present, that considers how mental disorders have historically challenged the ways in which humans have understood and valued their bodies, minds, and souls.